Physical Fitness and Locomotor Skills in Children With Esophageal Atresia-A Case Control Pilot Study - Tatjana T. König; Oliver J. Muensterer (Frontiers Media S.A., 2018)
Background: Patients with esophageal atresia (EA) often experience physical limitations. With increasing survival over the past decades, the focus in care shifted toward improving the long-term quality of life. We performed validated testing fitness and motor skills in children born with EA.Methods: Patients with EA were evaluated using the standardized Kinderturntest Plus/ Deutscher Motorik Test after caregiver's written consent. Test scores range from 1 to 5 (compared to an age- and gender matched standard population). Caregivers completed an online-questionnaire on patient history.Results: Seventeen patients (median age 7 [3-12] years) were included. Comorbidities were prematurity (54%), birth weight <1,500 g (23%), congenital heart disease (46%), developmental delay (38%), skeletal deformity (23%), and anorectal malformation (15%). The mean test score was significantly lower in children with EA (2.19) compared to a control group matched for age, gender, body weight, and -height, (2.75, p = 0.04), and the general population (3, p = 0.00). Distribution of patient scores was below the 41st performance percentile for gender and age in 54-63%. Caregivers identified notable deficits of strength and endurance. All but one patient complained about discomfort during physical exercise, most commonly respiratory distress (46%) and gastroesophageal reflux symptoms (31%). Notably, 93% of subjects participated in regular school physical education classes, and 86% participated regularly in additional organized sporting activities.Conclusions: Children after EA repair have decreased physical fitness and impaired locomotor function compared to the general population on a standardized test. Physical discomfort is frequent during exertion. To avoid demotivation, locomotor skill should be promoted at each individual's comfortable level.The study was registered at www.researchregistry.com (No. 3707).